Meraih Jiwa Korsa Berkarakter Cageur, Bageur, Pinter Melalui Tadarus di Universitas Ma’soem - Ida Rapida Djachrab; Ryzki Wiryawan (Masoem University, 2021)
This study aims to determine: 1) the character of cageur, bageur, pinter as part of the Al Ma'soem culture; 2) Tadarus activities at Ma'soem University; 3) The role of tadarus in developing the esprit de corps of employees. The research method is qualitative with an ethnographic approach in order to reveal the social and cultural meaning behind tadarus activities. Data collection techniques were carried out by participatory observation, in-depth interviews, literature studies and documentation studies. Determination of the sample using purposive sampling where sampling is done with certain considerations. Data analysis using the Spradley Model, was carried out in four stages: domain, taxonomy, componential, and cultural themes. The results showed that: 1) Cageur, bageur, pinter characters are the embodiment of the pioneering philosophy in order to create a balance between habluminalloh and habluminannas., 2) The benefits of tadarus for friendship, launch and get used to reading holy verses, the heart becomes calm and gives birth to a group of pioneers and followers, 3 ) Tadarus activities as organizational habits that are not directly related to work specifications can be a source of strength for the birth of the corps spirit of employees.